Robot‐assisted thoracic surgery for intercostal cavernous hemangioma. Issue 11 (19th April 2022) - Shoji, Fumihiro; Yamazaki, Koji; Kozuma, Yuka; Kawauchi, Shigeto; Takeo, Sadanori
Abstract: Intercostal cavernous hemangioma is extremely rare among benign vascular tumors. Achieving a definitive diagnosis preoperatively by radiographic examination alone is difficult; surgical resection is usually needed. Occasional cases are found as giant tumors, and some grow substantially during observation without treatment. Such tumors require extended surgical resection; however, small tumors can be completely resected by tumor extirpation alone. Thus, immediate surgical resection while the tumor is small might help to avoid invasive surgery. We herein describe cases of intercostal cavernous hemangioma with no invasion to the surrounding tissues, successfully treated by complete tumor resection using robot‐assisted thoracic surgery. Abstract : We herein describe two cases of intercostal cavernous hemangioma, successfully treated by complete tumor resection using robot‐assisted thoracic surgery. Although intercostal cavernous hemangioma is extremely rare, occasional cases are found as giant tumors which require extended surgical resection; however, small tumors can be completely resected by tumor extirpation alone. Thus, immediate surgical resection while the tumor is small might help to avoid invasive surgery.